العملات الرقمية للبنوك المركزية وانعكاساتها على الاقتصاد: Central bank digital currencies and their impact on the economy - بوثلجة عائشة, (Journal of North African Economies, 2025)
A significant number of central banks turned towards researching and studying the possibility of issuing a digital central currency, in order to counter the spread of cryptocurrencies that have spread widely and imposed themselves strongly on the global economic system, and because cryptocurrencies are issued without any authority, legal or monetary authority, they pose a threat to global economies. Through this research, we aim to introduce cryptocurrencies to their encrypted types issued by central banks and to study the characteristics of each of them. Focusing on the potential implications of the central digital currency's issuance on the economy, we have found that there are positive expectations for the economy but that there are challenges for economies behind the issuance of the digital currency to central banks. Therefore, a model for the issuance of the central digital currency must be developed in accordance with the characteristics of each economy because it has become inevitable imposed by monetary developments.